THE STRATEGY OF BUILDING A BRAND IMAGE THROUGH THE AVAILABILITY OF FACILITIES AND INFRASTRUCTURE IN AN EFFORT TO INCREASE SCHOOL COMPETITIVENESS - A Faisol Ashar; Sugiarto -; Eliana Sari (International Journal of Education, Information Technology, and Others, 2019)
The purpose of this research is to find out how schools make a brand image strategy utilizing available facilities and infrastructure to improve competitiveness. This study used a qualitative research method with a case study approach at Raden Umar Said Kudus Vocational School. The informants of this study were principals, teachers, students and school committees in Raden Umar Said Kudus Vocational School. The technique of collecting data is through observation and interviews. Based on the data analysis it was found that Raden Umar Said Kudus Vocational School in improving school competitiveness utilized the facilities and infrastructure owned. The utilization is carried out through sector strategy keys (key sector strategies) to build the brand image of the school in the community. The supporting factors are collaboration between Raden Umar Said Kudus Vocational School, the government, and the private sector, management of facilities and infrastructure, and utilization of facilities and infrastructure by students to create works. Meanwhile, the inhibiting factors are the lack of facilities and infrastructure technicians, the cost of maintaining facilities and infrastructure, and the lack of competency of teaching staff.